Metaphor, Transfer, and Translation in Plato’s Ion: The Postmodern Platonism of Percy Bysshe Shelley’s A Defence Poetry - Urquhart, Troy (Romanticism on the Net, 2003)
AbstractRecognizing Plato’s role as dramatist rather than as stenographer for Socrates reveals that the Ion presents a model for the creation and transfer of meaning that is remarkably similar to that described by Shelley’s A Defence of Poetry. Even though Socrates criticizes the poet for diluting the truth, Plato’s text, through its metaphor of the iron rings and through its own structure as a dramatic dialogue, presents and itself serves as a model of how meaning is created, a model which serves as a basis for Shelley’s text. The Ion’s iron rings suggest the interminable progression of metaphor by which meaning is constructed and kept current, and this view of language, in which meaning is constructed by the poet rather than reflected or distorted, points to a reprieve for poetry from Socrates’s banishment of it in Republic X.